2019
DOI: 10.1007/s42000-019-00155-z
|View full text |Cite
|
Sign up to set email alerts
|

The association between vitamin D status and infectious diseases of the respiratory system in infancy and childhood

Abstract: Purpose Respiratory tract infections (RTIs) are a major cause of illness worldwide and the most common cause of hospitalization for pneumonia and bronchiolitis. These two diseases are the leading causes of morbidity and mortality among children under 5 years of age. Vitamin D is believed to have immunomodulatory effects on the innate and adaptive immune systems by modulating the expression of antimicrobial peptides, like cathelicidin, in response to both viral and bacterial stimuli. The aim of this review is t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(49 citation statements)
references
References 89 publications
(89 reference statements)
0
45
0
1
Order By: Relevance
“…Although the mechanism of the vitamin D effect on immunity is complex, currently available data support the hypothesis that cathelicidins and defensins can reduce viral replication rates and the levels of proinflammatory cytokines. 76 Studies in small children with influenza have shown that high doses of vitamin D resulted in fast relief from symptoms, a rapid decrease in viral load, and early disease recovery. In addition, high daily doses of vitamin D have been shown to be effective in the prevention of seasonal influenza.…”
Section: What Mechanisms Play a Role In The Atypical Picture Of Coronmentioning
confidence: 99%
“…Although the mechanism of the vitamin D effect on immunity is complex, currently available data support the hypothesis that cathelicidins and defensins can reduce viral replication rates and the levels of proinflammatory cytokines. 76 Studies in small children with influenza have shown that high doses of vitamin D resulted in fast relief from symptoms, a rapid decrease in viral load, and early disease recovery. In addition, high daily doses of vitamin D have been shown to be effective in the prevention of seasonal influenza.…”
Section: What Mechanisms Play a Role In The Atypical Picture Of Coronmentioning
confidence: 99%
“… 84 , 85 A correlation between increased incidence of COVID-19 and insufficient vitamin D concentrations in patients was further supported by Zhang and Liu, 12 who confirmed that middle-aged to elderly people recently affected by COVID-19 in China had low vitamin D levels. However, Zisi et al 86 has highlighted the need to validate whether vitamin D supplementation is beneficial for COVID-19 patients, as conflicting results were noted in some studies, while Grant et al 13 suggested vitamin D supplementation as a therapeutic option for the treatment of COVID-19.…”
Section: Immune-boosting Role Of Vitaminsmentioning
confidence: 99%
“…Similar to statins, Vitamin D, a steroid hormone made in the skin by the action of sunlight, may also have anti-inflammatory and immune-regulatory properties [135,136]. In COVID-19, there is currently no reports on prospective studies examining supplementation with vitamin D or its analogs and outcomes in patients but a recent study by Hastie et al [137] showed that vitamin D deficiency was associated with higher risk of SARS-CoV-2 infection; however the authors claim this was not causal.…”
Section: Meta-analyses Of Clinical Studies Of Covid-19 Patients Receimentioning
confidence: 99%
“…In COVID-19, there is currently no reports on prospective studies examining supplementation with vitamin D or its analogs and outcomes in patients but a recent study by Hastie et al [137] showed that vitamin D deficiency was associated with higher risk of SARS-CoV-2 infection; however the authors claim this was not causal. Based on preclinical and clinical studies suggesting the vitamin D deficiency is associated with increased acute respiratory tract infections [136,138], further clinical trials on whether vitamin D supplementation is beneficial in preventing COVID-19 infections are pending. However, as a precautionary measure, the UK government has proactively issued a recommendation for its population to take Vitamin D supplements during the COVID-19 pandemic [139,140].…”
Section: Meta-analyses Of Clinical Studies Of Covid-19 Patients Receimentioning
confidence: 99%